Role of Haematologist in Radiologic and Nuclear Events - Muhammad Abdul Naeem and Muhammad Usman (Journal of Rawalpindi Medical College, 2009)
In Nuclear disasters whether they happen in war or occur accidentally the results are always very devastating. Following a Nuclear disaster all doctors, along with haematologists would be called out to participate. It is imperative to develop treatment guidelines for post radiation emergencies. Though such guidelines are available all around the world we outline the current plans for event response including catastrophic events that would require extensive support. The threat of possible nuclear disaster whether due to detonation of a nuclear device or due to accidents in handling of the radioactive materials requires that we develop and implement a plan of response.1 More than 400 radiologic accidents have occurred since 1944, resulting in more than 3000 significant exposures. Approximately 10 million “sealed sources” of radioactive material (e.g., cesium-137, cobalt-60) are used for medical, industrial, agricultural, and research purposes worldwide. More than 600 of these were lost or stolen since 1995 and less than half were eventually recovered. The haemopoietic system is the most rapidly dividing tissue of the body and as such the most vulnerable of all and most radiosensitive. Exposure of the haemopoietic stem cell as well as the progenitor cells results in their exponential death. The haemopoietic progenitor cells cannot survive a dose of >2-3 Gray (Gy).It results in haematological disaster in subsequent days including lymphopenia, bone marrow atrophy ,pancytopenia and bleeding which all contribute to its lethality. 2 Models suggest that, if a device similar to the bomb detonated over Hiroshima struck a city such as Karachi up to 175 000 victims would require intensive medical care and 300 000 would require management for myelosuppression. 3 Establishing National Haematology Radiation Injury Treatment Organization It is purposed that a Pakistan Haematology Radiation Injury Treatment Organization be established on the lines of Radiation Injury Treatment